2022
DOI: 10.3390/jcm11051415
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health-Related Quality of Life in Patients after Stroke—A Systematic Review

Abstract: Objectives: Aim of this systematic review was to assess oral health-related quality of life (OHRQoL) of patients after stroke. Methods: The systematic literature search was performed on December 2021 based on PubMed, Medline, Web of Science, and Scopus, with the search terms: “oral health-related quality of life” AND stroke OR apoplexy OR ischemic stroke OR apoplectic insult. Articles exclusively examining patients after stroke and reporting a well-documented and valid OHRQoL measurement were included. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
2
2
0
Order By: Relevance
“…A recent systematic review also reported a decrease in health-related quality of life in the stroke patients. 22 Consistent with the previous literature, a decrease in health-related quality of life in the stroke patients was also observed compared with the healthy controls in the present study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…A recent systematic review also reported a decrease in health-related quality of life in the stroke patients. 22 Consistent with the previous literature, a decrease in health-related quality of life in the stroke patients was also observed compared with the healthy controls in the present study.…”
Section: Discussionsupporting
confidence: 93%
“…In their study comparing hospitalised stroke patients and a healthy control group, Schimmel et al 21 observed higher OHIP‐14 values than in the control group, and reported lower oral health‐related quality of life in the stroke patients. A recent systematic review also reported a decrease in health‐related quality of life in the stroke patients 22 . Consistent with the previous literature, a decrease in health‐related quality of life in the stroke patients was also observed compared with the healthy controls in the present study.…”
Section: Discussionsupporting
confidence: 92%
“…While for a definitive confirmation of the hypothesis of this review, a control group would be needed, it was decided to include studies without a control group to increase the number of included studies and, thus, the ability to draw conclusions. This was performed similarly to previous studies [ 40 , 47 ]. Most studies showed a moderate quality ( Table 4 ).…”
Section: Discussionmentioning
confidence: 94%
“…Finally, by regression analysis, we found that age, toothache, evaluation of dental and oral status, reason for not having visited the dentist in the past year, and time since the last visit to the dentist were factors influencing OHRQoL among patients hospitalised with a stroke in this study. This suggests to us that health care professionals should support oral hygiene and dental visits and promote oral health education for patients to improve their oral health and OHRQoL [ 59 ].…”
Section: Discussionmentioning
confidence: 99%